Studi Geologi dan Prospek Kualitas Andesit Di Daerah Nagari Tambang Kec IV Jurai Pesisir Selatan Sebagai Bahan Bangunan dan Tambang - Aan Kurniawan; Ansosry Ansosry (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. Calculation of resources plays an important role in determining the amount of reserves and determining the amount, quality and ease of commercial exploration of a sediment. Because the results of resource calculations can be continued on a good calculation of reserves later to be able to determine the investment that will be planted by investors, how to mine even in estimating the time needed by the company in carrying out its mining business. The purpose of this study is to determine the amount of andesite indicated by the method of cross section and contour in Nagari Tambang Pesisir Selatan / West Sumatra. Data processing is done with the help of mine software in making contours, incisions and calculations. Determination of research boundaries is based on the presence of outermost outcrops.The results of the research have been carried out with the cross section method, which is making incision lines that cut the overburden, then calculating the area of each incision and finally the volume can be determined using the inter-incision distance and 9,079,700 tons and the contour method namely using each contour to calculate the area and volume of each contour interval, the andesite indicated amounted to 8,435,602.5 tons with a total OB volume of 43,650 m³.Keywords: Resources, Andesite, quality, cross section, contour